3-rd Spring School on Acousto-Optics and Applications Gdańsk–Wieżyca, May 29-31, 1986 // Istituto di Acustica ,,O. M. Corbino’’, 50th anniversary celebration, Rome, Italy, 28-30 april 1987 - ŚLIWIŃSKI, A.; GIUA, P. E. (Archives of Acoustics, 1986)
The 3-rd School on Acousto-optics and Applications like the two previous ones (in 1980 – Arch. Acoust. 6 (1981) 85-86 and in 1983 – Arch. Acoust. 9 (1984) 382-382) took place at Wieżyca near Gdańsk in the recreation centre of the Gdynia Shipyard. The School was organized by the Institute of Experimental Physics, University of Gdańsk in cooperation with the Section of Quantum and Molecular Acoustics of the Polish Acoustical Society and with support by the Institute of Fundamental Technological Research, Polish Academy of Sciences. The “Istituto di Acustica O. M. Corbino” of the Italian National Research Council will celebrate its Fiftieth Anniversary of activity with a 3 days meeting (28-30 april 1987) in Rome, Italy.